EFEKTIFITAS PROMOSI KESEHATAN DENGAN PENDEKATAN FEAR-APPEAL MESSAGE UNTUK MENINGKATKAN TINGKAT KEPATUHAN MASYARAKAT DI ERA NEW NORMAL - Heni Frilasari; Heri Triwibowo (LPPM Akper Dian Husada Mojokerto, 2021)
The COVID-19 pandemic is currently occurring in various regions of the world, including Indonesia. The Covid-19 pandemic forces policy makers in Indonesia to implement various policies, such as large-scale restrictions to the implementation of the new normal. However, all government control programs require full awareness and support from all parties, including the community. The purpose study to identify effectiveness of health promotion with the fear-appeal message approach to increasing level of compliance community in era new normal. The research design used pre-experimental study with probability sampling. Data analysis was performed using paired t test. The results showed that there was a significant difference level of compliance in the intervention group before and after being given health promotion with the appeal message approach (p value <0.005). The paired t test results showed the experimental group ρ value = 0,000, and ρ control group = 0,001 α = 0,05 so that ρ <α There was the influence level of compliance after being given health promotion with the appeal message approach. Providing education to experimental groups with video media is more effective The approach to fear-appeal message is able to increase level of compliance in community with health protocols in the era new normal so that the incidence of new COVID-19 cases decreases